2014
DOI: 10.1007/s11046-014-9731-y
|View full text |Cite
|
Sign up to set email alerts
|

Wild Animals as Sentinels of Paracoccidioides brasiliensis in the State of Rio Grande do Sul, Brazil

Abstract: Paracoccidioides brasiliensis, a dimorphic pathogenic fungus, causes the principal form of systemic mycosis in Brazil. The literature furnishes only limited data on the ecology of this fungus in the state of Rio Grande do Sul, the southernmost state of Brazil. The purpose of this study was to evaluate the prevalence of fungal infection in wild animals, using serological tests and using the animals as sentinels of the presence of P. brasiliensis in three specified mesoregions of Rio Grande do Sul. A total of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…Although infection by P. brasiliensis has been demonstrated in several wild animal species [15,16,26,[31][32][33], this is the first evidence of PCM in Akodon sp., E. russatus, T. nigrita and O. nigripes. The negativity observed in histopathological examination, immunodiffusion and culture probably is due to the lower sensitivity of these methods.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Although infection by P. brasiliensis has been demonstrated in several wild animal species [15,16,26,[31][32][33], this is the first evidence of PCM in Akodon sp., E. russatus, T. nigrita and O. nigripes. The negativity observed in histopathological examination, immunodiffusion and culture probably is due to the lower sensitivity of these methods.…”
Section: Discussionmentioning
confidence: 68%
“…An epidemiological study with several species of wild mammals from a Brazilian zoo showed higher positivity to paracoccidioidin skin test in terrestrial animals (82.98 %) than arboreal animals (22.45 %), reinforcing that soil is the habitat of P. brasiliensis [32]. A seroepidemiological study evaluated P. brasiliensis infection in several wild animal species from the State of Rio Grande do Sul, Brazil, and showed positivity in animals from the orders Artiodactyla, Rodentia, Xenarthra, Carnivora, Marsupialia and Primata [33].…”
Section: Discussionmentioning
confidence: 91%
“…Seropositivity for IgG anti‐CFA of P. lutzii was detected in 13% of horses (26/200), 26.5% of dogs (52/196) and 31.8% of wild mammals (27/85). Of these, sera from 15 horses, 22 dogs and 17 wild mammals also had IgG anti‐gp‐43 from P. brasiliensis . However, seropositivity only for P. lutzii occurred in 5.5% (11/200) of horses, 15.3% (30/196) of dogs and 11.8% (10/85) of wild animals (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…According to recent studies, P. lutzii has its epicentre in the central‐west region of Brazil, unlike P. brasiliensis , which was also described in the south and southeast regions of the country . However, P. lutzii was reported in the Amazon region .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation